2021
DOI: 10.3389/fbioe.2021.711534
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of Carbon Dot – Iron Oxide Nanoparticles for Fluorescence Imaging and Therapy

Abstract: Fluorescence microscopy is commonly used to image specific parts of a biological system, and is applicable for early diagnosis of cancer. Current fluorescent probes, such as organic dyes and quantum dots, suffer from poor solubility and high toxicity, respectively, demonstrating a need for a colloidal stable and non-toxic fluorescent probe. Here we present an iron oxide and carbon dot (CD) based nanoparticle (CNPCP) that displays optical properties similar to those of conventional fluorescent probe and also ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 53 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…In another study using microwave irradiation, fluorescent CDs were prepared using glucosamine onto a PEG @ chitosan co-polymer layer. The resultant CDs could show excellent chemical stability, good fluorescence intensity, and excitation-dependent fluorescence in biological matrices [142].…”
Section: Microwave-assisted Methodsmentioning
confidence: 99%
“…In another study using microwave irradiation, fluorescent CDs were prepared using glucosamine onto a PEG @ chitosan co-polymer layer. The resultant CDs could show excellent chemical stability, good fluorescence intensity, and excitation-dependent fluorescence in biological matrices [142].…”
Section: Microwave-assisted Methodsmentioning
confidence: 99%
“…Chung et al, used microwave irradiation to create fluorescent iron oxide and carbon dots-based nanoparticles for cancer cell fluorescence imaging and treatment. The use of these QDs as fluorescent probes in cancer cell lines revealed that they were less hazardous and allowed for quick and quantitative imaging (Chung and Zhang, 2021). Ma et al, designed a fluorescent probe for detecting protein tyrosine kinase 7 in the peripheral circulation using multi-carbon dots and an aptamer-based signal amplification ratiometric.…”
Section: Applications Of Quantum Dots In Cancer Treatment Early Diagnosis Of Cancer By Quantum Dotsmentioning
confidence: 99%
“…Traditional semiconductor QDs are composed of group II-VI or III-V elements and usually contain toxic heavy metal ions, greatly limiting their applications in biological and environmental fields. As such, the development of metal-free fluorescent QDs such as carbon QDs ( Chung and Zhang, 2021 ; Sun et al, 2006 ; Liao et al, 2016 ), graphene QDs ( Kalita et al, 2016 ; Zhou et al, 2017 ), and silicon QDs ( Warner et al, 2005 ) has attracted more and more attention.…”
Section: Introductionmentioning
confidence: 99%